Equilibrium and kinetic behavior on cadmium and lead removal by using synthetic polymer - Mohd Zahri, Nur Amirah; Md Jamil, Siti Nurul Ain; Abdullah, Luqman Chuah; Sim, Jia Huey; Choong, Thomas Shean Yaw; Mobarekeh, Mohsen Nourouzi; Mohd Rapeia, Nur Salimah (Elsevier, 2017)
It is known that synthetic polymer plays a big role in various applications. One of its potentials is to remove heavy metal ions through single batch adsorption. Adsorption behavior and mechanism of synthetic polymer are the two main focuses in this research. The synthetic polymer of Poly(AN-co-AA) has been successfully polymerized, modified with hydroxylamine hydrochloride and removed Cd2+ and Pb2+. The poly(AN-co-AA) and amidoxime (AO) modified poly(AN-co-AA) were characterized by Fourier Transform Infrared Analysis (FTIR), microanalysis, Scanning Electron Microscopy (SEM) and Thermogravimetry (TGA). At pH 9, the percentage removal for Cd2+ (90%) and Pb2+ (98%) were the highest with adsorbent dosage at 4 gL−1 and 8 g L−1, respectively. The experimental data for Cd2+ (20 mg g−1) and Pb2+ (125 mg g−1) were fitted well by Sips and Freundlich isotherms model, respectively. The adsorption rate for both Cd2+ and Pb2+ were stated by using Lagergren pseudo-first order.